Compiler construction : 22nd International Conference, CC 2013, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2013, Rome, Italy, March 16-24, 2013. Proceedings - Bosschere, Koen; Jhala, Ranjit (Lecture Notes in Computer Science, 2013)
This book constitutes the proceedings of the 22nd International Conference on Compiler Construction, CC 2013, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2013, which took place in Rome, Italy, in March 2013. The 13 papers presented in this book were carefully reviewed and selected from 53 submissions. They have been organized into five topical sections on register allocation, pointer analysis, data and information flow, machine learning, and refactoring.